THE STATE OF ARTERIAL HYPERTENSION DIAGNOSTICS AND TREATMENT, ACCORDING TO THE RESULTS OF THE POLL AMONG PHYSICIANS OF VOLGOGRAD AND VOLGOGRAD REGION - S. Y. Martsevich; N. S. Oganisyan; N. A. Dmitrieva; A. V. Klimakov (Столичная издательская компания, 2015)
Aim. Assessment and quality of diagnostics of treatment of patients with arterial hypertension (AH) and their conformity with international and national recommendations on AH.Material and methods. The poll among physicians of Volgograd and Volgograd region, who took part in the regional conference, devoted to the problems of AH, was carried out in April 2004. The questionnaire included 13 questions about peculiarities of AH patients' management 128 physicians took part in the poll, from them 90 thetapeutists (general physicians), 24 cardiologists, and 14 physicians of different therapeutic specializations.Results. Variability of conceptions of physicians on some principals of diagnostics and treatment of AH patients is revealed. Insufficient knowledge of criteria for division patients according to the risk category of cardiovascular complications. The same is observed for definition of AH grade according to the blood pressure level, and of the main approaches AH patients treatment. From all the questioned physicians only 25.2% correctly evaluated the risk level of cardiovascular diseases, 21% of physicians wrongly assessed the AH grade according to the blood pressure Level.Conclusion. Results, show that real practice of diagnostics and treatment of AH significantly deviates from international and national recommendations on AH.